Peregrinus Sum, Studies in History of Hungarian-Dutch Cultural Relations in Honour of Ferenc Postma on the Occasion of His 70th Birthday: Szerkesztette Margriet Gosker, Monok István, Budapest-Amsterdam, 2015, 292 lap - Doedens, Jaap (Gerundium, 2015)
Peregrinus Sum, Studies in History of Hungarian-Dutch Cultural Relations in Honour of Ferenc Postma on the Occasion of His 70th Birthday - recenzió